Pengaruh Penggunaan Media Video Tutorial di Aplikasi TikTok terhadap Hasil Belajar Materi Menggambar Komik Kelas VIII SMPN 1 Bathin Solapan - Nurul Huda; Yusron Wikarya (Journal on Education, 2024)
This study covers all VIII grade students of SMPN 1 Bathin Solapan, consisting of 110 students, and aims to determine the difference in the use of video tutorial media in the TikTok application with conventional media on the learning outcomes of comic drawing material. samples used in class VIII 4 and VIII 2. Random sampling technique This type of research uses quantitative research methods with the type of pseudo experiment (Quasi Experiment). The data needed in this study are primary data in the form of pre-test and post-test results. The data analysis was carried out by normality test, homogeneity test, and hypothesis testing stage using SPSS version 25. Based on data processing, it is known that there are differences in the learning outcomes of students who are taught using video tutorial media in the TikTok application with the learning outcomes of students using conventional media, namely t coun= 4.924 and t table = 2.064 at the alpha = 0.05 level. This shows that t count> t table, it can be concluded that learning using video tutorial media in the TikTok application has a significant difference to the learning outcomes of drawing comics in class VIII SMPN 1 Bathin Solapan.